Assessment of Policy and Legal Frameworks of Urban Green Infrastructure Development: Republic of Guinea - Kandas Keita; Sory Kourouma (Buildings, 2023)
Urban green infrastructure has become crucial to sustainable cities’ development because it offers many advantages, including better environmental quality, increased social well-being, and increased economic prosperity. The evaluation and monitoring of the implementation of policies are essential elements of the development of urban green infrastructure because they demonstrate the will of political decision-makers to assess the implementation’s success and adapt it to the observed need. This article sets out existing institutional structures, institutional plans, and institutional policies linked to creating urban green infrastructure in three study cities: Conakry, Kankan, and Dubreka. The collected data were analyzed using descriptive statistics and policy analysis. The study used primary data collection methods, including questionnaires and interviews with key informants, to gather first-hand information from decision-makers, planners, managers, and other organizations involved in developing and managing urban green infrastructure at regional and local levels. In addition, this study used primary data collection, facilitating the collection of first-hand information reinforced by questionnaires. A simple random sampling method was also adopted, which improved the selection of a sample of 330 respondents. Most government officials and academics agree that current policies regarding green urban infrastructure have not been implemented. The study has identified several shortcomings in existing political and legal frameworks, in particular the lack of coordination and coherence between the ministries and the government agencies involved, insufficient financial and human resources, the lack of attention, the lack of transparency in the process of developing policies and regulations, the low involvement of the private sector, the need to strengthen technical capacity, and poor urban green infrastructure strategies. These actions are necessary to develop essential policies and procedures that improve the development of green urban infrastructure. In order to overcome these obstacles, efforts must be made to improve coordination and collaboration between stakeholders, strengthen technical capacity, increase public participation, and improve transparency in the process of policies and regulation.